2021
DOI: 10.1097/j.pain.0000000000002421
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyltransferase 7 modulates neuronal excitability by interacting with NaV1.9

Abstract: Human Na V 1.9 (hNa V 1.9), encoded by SCN11A, is preferentially expressed in nociceptors, and its mutations have been linked to pain disorders. Na V 1.9 could be a promising drug target for pain relief. However, the modulation of Na V 1.9 activity has remained elusive. Here, we identified a new candidate Na V 1.9-interacting partner, protein arginine methyltransferase 7 (PRMT7). Whole-cell voltage-clamp recordings showed that coelectroporation of human SCN11A and PRMT7 in dorsal root ganglion (DRG) neurons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“… 1 , 2 Known substrates methylated by PRMT7 include core histones (H2A, H2B, H3, and H4), Wnt signaling molecules, and transcription factors, involving PRMT7 in a wide range of biological processes, such as gene expression and epigenetic regulation, cell differentiation, muscle and neuron development, and adipogenesis. 3 , 13 , 14 A significant number of genes involved in chromatin regulation have been associated with neurodevelopmental disorders, collectively known as chromatinopathies. 15 PRMT7- related disorder shares some overlapping phenotypes with chromatin-related neurodevelopmental disorders, particularly short stature and growth delay and presence of major craniofacial dysmorphisms and skeletal and digital abnormalities (eg, Wiedemann-Steiner syndrome and Chung-Jansen syndrome).…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Known substrates methylated by PRMT7 include core histones (H2A, H2B, H3, and H4), Wnt signaling molecules, and transcription factors, involving PRMT7 in a wide range of biological processes, such as gene expression and epigenetic regulation, cell differentiation, muscle and neuron development, and adipogenesis. 3 , 13 , 14 A significant number of genes involved in chromatin regulation have been associated with neurodevelopmental disorders, collectively known as chromatinopathies. 15 PRMT7- related disorder shares some overlapping phenotypes with chromatin-related neurodevelopmental disorders, particularly short stature and growth delay and presence of major craniofacial dysmorphisms and skeletal and digital abnormalities (eg, Wiedemann-Steiner syndrome and Chung-Jansen syndrome).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what gene and protein targets are involved in PRMT4-induced arginine methylation of histone and non-histone proteins in neuropathic pain. In addition, PRMT7 interacts with Na V 1.9 ( Scn11a ) in the mouse DRG and methylates the arginine 519 (R519) residue in its hLoop1 . This increased methylation may facilitate the trafficking of Na V 1.9 to the cell membrane, augmenting neuronal excitability and nerve injury-induced neuropathic pain.…”
Section: Role Of Histone Modifications In Neuropathic Painmentioning
confidence: 99%
“…In addition, PRMT7 interacts with Na V 1.9 (Scn11a) in the mouse DRG and methylates the arginine 519 (R519) residue in its hLoop1. 52 This increased methylation may facilitate the trafficking of Na V 1.9 to the cell membrane, augmenting neuronal excitability and nerve injury-induced neuropathic pain.…”
Section: Role Of Histone Modifications Inmentioning
confidence: 99%
“…PRMT7 plays a significant role in promoting the progression of different types of malignancies, such as leukemia, melanoma, nonsmall-cell lung cancer, and breast cancer . Additionally, studies have reported that PRMT7 regulates neuronal excitability by modulating NaV1.9 currents and contributes to cardiac hypertrophy and fibrosis through dysregulation of β-catenin signaling pathway . Moreover, PRMT7 is involved in regulating oxidative metabolism processes as well. , However, the specific role played by PRMT7 in SAP remains unknown.…”
Section: Introductionmentioning
confidence: 99%